Sistem Pendukung Keputusan Pemilihan Laptop Untuk Kebutuhan Kuliah Metode Simple Additive Weighting (SAW) - Muhammad Syahril; Imam Suharjo (Journal Of Information System And Artificial Intelligence, 2021)
In this study, the authors aim to design and build a decision support system for election decisions on a laptop, the method I use is the Simple Additive Weighting (SAW) method. There are six criteria that the author uses, namely price, price, processor brand, hardiks, ram, VGA, screen size. The use of a Decision Support System (DSS) is expected to help prospective customers to more easily consider choosing a laptop that suits their wishes. Based on the 26 submitted data, 22 laptops (84.61%) were suitable and 4 laptops (15.38%) were unsuitable.